2009
DOI: 10.1002/app.30770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the electron donor structure on the shelf‐lifetime of visible‐light activated three‐component initiator systems

Abstract: In this study, we investigated the effect of electron donor structures on the shelf life of three-component initiator systems which also included methylene blue (MB) as a photosensitizer and diphenyl iodonium salt (DPI) as an electron acceptor. For this research, N-phenylglycine (NPG), N-methyldiethanolamine (MDEA), N,N-diisopropyl-3-pentylamine (DIPA), and 1,4-diazabicyclo[2.2.2]octane (DABCO) were used as electron donors, with different of proton transfer efficiencies and radical/cation persistence. To aid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…For all complexes, the Ir /Iod interaction reactions are highly favorable according to the highly negative free energy change (Table ; e.g., Δ G = −1.28 and −1.41 eV for Ir_3 and Ir_12 , respectively; using E red (Ph 2 I + ) = −0.2 V) . The same holds true for the Ir /MDEA reactions (e.g., Δ G = −0.89 eV for Ir_12 ; using E ox (MDEA) = 1 V) …”
Section: Resultsmentioning
confidence: 73%
“…For all complexes, the Ir /Iod interaction reactions are highly favorable according to the highly negative free energy change (Table ; e.g., Δ G = −1.28 and −1.41 eV for Ir_3 and Ir_12 , respectively; using E red (Ph 2 I + ) = −0.2 V) . The same holds true for the Ir /MDEA reactions (e.g., Δ G = −0.89 eV for Ir_12 ; using E ox (MDEA) = 1 V) …”
Section: Resultsmentioning
confidence: 73%
“…The photoinitiation mechanism in the presence of MB/ TEOA or AO/TEOA involves the electron transfer, followed by a proton transfer from the tertiary amine to the dye leading to the formation of amine radical (TEOA. ), which will initiate the polymerization, and the dye radical which acts as a terminating agent [12,30]. Figure 7b shows that the monomer conversion is about 90% in the first 35 s of irradiation, when AO photosensitizer is used, whereas is about 40% in the case of MB.…”
Section: Phototransformation Of Mb and Aomentioning
confidence: 99%
“…9. After irradiation, the excited dye reacts with amine to form the amine radical cation, this reaction is followed by proton transfer from the amine to the dye, leading to the formation of free radical active center capable to initiate polymerization, and the dye radicals act as terminating agents, according to the reaction below: It has been reported that the efficiency of amine as coinitiator depends on the radical cation persistence and the proton transfer ability [30,33]. More the proton transfer is delayed more the radical cation is persistent.…”
Section: Synergy Between Mb Dye and Co-initiatorsmentioning
confidence: 99%
“…The three‐component systems showed an approximately fivefold increase in the polymerization rate. Three‐component photoinitiator systems including a light‐absorbing photosensitizer, an electron donor, and an electron acceptor for visible light‐activated free‐radical polymerization were also intensively investigated by Stansbury and coworkers 198–202. They used xanthene dyes (e.g., rose bengal and fluorescein), a phenazine dye (methylene blue), a porphin dye (5,10,15,20‐tetraphenyl‐21H,23H‐porphin zinc; Scheme ), or CQ as photosensitizer, various amines as electron donors, and a diphenyliodonium salt as electron acceptor.…”
Section: Restorative Compositesmentioning
confidence: 99%